Short protocols in protein science : a compendium of methods from current protocols in protein science. - Coligan, John E., ....-; Dunn, Ben M., 1945-; Speicher, David W., ....- ([s.l.] : Wiley, 2003)
Short Protocols in Protein Science provides condensed descriptions of more than 500 protocols compiled from Current Protocols in Protein Science. Drawing from both the original "core" manual as well as the quarterly update service, this compendium includes all step-by-step descriptions of the principal methods covered in Current Protocols in Protein Science.